STUDI TINGKAT PENCEMARAN AIR PENCUCIAN KACANG KORO (Vigna unguiculata L) DI SALURAN IRIGASI TIMUHUN DESA NYANGLAN KABUPATEN KLUNGKUNG - Ariasih, M; Mahendra, M S; Mahardika, I G (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Timuhun irigation channel is one of the irigation water sources which is located in the District of BanjarangkanKlungkung Regency of Bali Province which is flowing from its origin at Bubuh River which flows passses three villagesof Bangbang, Nyanglan, and Timuhun villages.The objective of this study was to determine the properties of pollutant of kacang koro as well as to determine theperception of the owner/industry workers and the community at the Timuhun village produced during the washingprocess.This study was conducted from December 2007 to Januari 2008. The sample of the irigation water of Timuhunwas taken from nine locations and the sample of the waste water was taken from three locations. The index of thepollution was calculated and compared to the Governor Regulation Number 8 of 2007 while the community perception onthe waste impact of the kacang koro washing was analyzed using percentage formulae.The finding of the study shows that the pollutant properties of of the waste water have exceeded the maximumlevel of quality standard covering parameters of TSS, COD, BOD5 and ammonia. The pollution of the Timuhun irigationby the waste water from the kacang koro washing is indicated by the high property of the water quality parameter onBOD5 and COD. Based on the pollution index (PI), it was found that the water quality of Timuhun irigation reached amild pollution in all criteria of water quality of class I, class II, class III, class IV except the origin location which is stillin good condition. The perception analysis on the waste water impact showed that the community of Timuhun have a badperception, so the owner and industry workers have a good perception.
Keywords: waste, pollution, water quality, pollution index